Sociology of Education Today
XIV, 259 p.
Keywords: It is almost twenty years since Macmillan published Jack Demaine's Contemporary Theories in the Sociology of Education . This completely new book brings together important recent work of the most prominent sociologists working in the field of education today, and reaffirms the reputation of sociology of education as an international discipline at the forefront of original research and analysis. The book examines a wide range of empirical issues and different theoretical perspectives.